Magnetic order in the S=1/2 two-dimensional molecular antiferromagnet copper pyrazine perchlorate Cu(Pz)(2)(ClO4)(2) - Lancaster, T; Blundell, S; Brooks, M; Baker, P; Pratt, F; Manson, J; Conner, M; Xiao, F; Landee, C; Chaves, F; Soriano, S; Novak, M; et al. (2007)
We present an investigation of magnetic ordering in the two-dimensional S= 2 quantum magnet Cu (Pz)2 (Cl O4) 2 using specific heat and zero-field muon-spin relaxation (μ+ SR). The magnetic contribution to the specific heat is consistent with an exchange strength of 17.7 (3) K. We find unambiguous evidence for a transition to a state of three-dimensional long-range order below a critical temperature TN =4.21 (1) K using μ+ SR even though there is no feature in the specific heat at that temperature. The absence of a specific heat anomaly at TN is consistent with recent theoretical predictions. The ratio of TN J=0.24 corresponds to a ratio of intralayer to interlayer exchange constants of J′ J=6.8× 10-4, indicative of excellent two-dimensional isolation. The scaled magnetic specific heat of [Cu (Pz)2 (H F2)] B F4, a compound with an analogous structure, is very similar to that of Cu (Pz)2 (Cl O4) 2 although both differ slightly from the predicted value for an ideal 2D S= 2 Heisenberg antiferromagnet. © 2007 The American Physical Society.